Apocrine hidrocytoma in an Awassi sheep (Veterinary Science Development, 2014)
Hidrocytomas are benign cystic lesions of sweat apocrine glands. It is a recognized condition in cats and dogs, but has never been reported in sheep. In this case, a 5-year-old Awassi ewe was presented for ocular evaluation. The left eye had a 1.0-cm-diameter dome shaped mass containing clear fluids and was protruded from the palpebral eyelid margin near the lateral canthus. The cyst was surgically removed and revealed apocrine hidrocytoma via histopathology. Seven months post-surgery, neither cyst recurrence nor additional masses were present. To the best of our knowledge, this is the first case of apocrine hidrocytoma in sheep.